Knowledge management in academia: survey, analysis and perspective. (7th March 2006) - Tian, Jing; Nakamori, Yoshiteru; Xiang, Jianwen; Futatsugi, Kokichi
Research on knowledge management in academia has become a hot issue and a promising research area. Most research, however, has focused on general educational organisations, such as high schools and universities. This paper concentrates on understanding the problems of knowledge creators per se instead of the general student population, as disclosed by a survey of the scientific knowledge management and creation process at the Japan Advanced Institute of Science and Technology (JAIST). By using comparison, classification, cross tabulation, and other analysis methods, some subtle issues and hidden problems have been discovered in this survey, such as the unevenness of technical support among different schools, ignorance of cooperation as one source of knowledge, different requirements of foreign and Japanese researchers, and so on. Along with these findings, we also present our corresponding analysis and suggestions for more effective knowledge management and better creativity support, and some perspectives and future research directions in this field.